ANALISIS PROFIL PENGARUH BAHAN ORGANIK TERHADAP KONSENTRASI BESI FERRO DAN SERAPANNYA DI LAHAN RAWA PASANG SURUT - Annisa, Wahida; Subagio, Herman (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2016)
This study aimed to determine the similarity of the characteristics of each type of organic matter in suppressing the solubility of iron in soil and absorption in plants. This research was conducted in two stages. The first stage was conducted in the greenhouse to study the effect of organic matter to iron solubility in acidic sulphate soil. The research used a factorial design with 1 control and 3 replications. The first factor was type of organic matter used, B1 = rice straw; B2 = weeds; B3 = Combination of 50% rice straw and 50% weeds. The second factor was the incubation period of organic matter I1 = 2 weeks, I2 = 4 weeks, I3 = 8 weeks, and I4 = 12 weeks. The second stage was analyzing the profiles of the type of organic matter in order to evaluate the similarity of the characteristics of each type of organic matter. Based on the profile alignment, it was found that the three types of organic matter were not aligned. The types of organic matter had different roles in suppressing the solubility of iron in soil and its absorption in plants. There is a need to do a comparative analysis with Tukey method to the three types of organic matter.